Effect of Sc and Zn doping on structure and electro-optical behavior in c-BiAlO3: A DFT trial. (1st August 2022) - Rizwan, Muhammad; Farman, Muhammad; Akgül, Ali; Ayub, Asma; Usman, Zahid
Abstract: Density Functional Theory (DFT) is an attractive route to search for new substitute lead free perovskite materials for linear and non-linear optics, with superior properties similar to PZT materials. We consider environment friendly facile c-BiAlO3 piezoelectric material, where Bi is substituted by transition metals (Sc, Zn). The effect of these dopant on the structural, electronic and optical properties of c-BiAlO3 are investigated by using generalized gradient approximation and ultrasoft pseudopotential method as implemented in CASTEP. Structural properties experience reciprocal effect on lattice constant as a function of ionic size of Impurities. In addition, a transition of indirect band gap of c-BiAlO3 to the direct one is obtained after TM impurity substitution. The optical properties such as absorption, energy loss, refractive index, dielectric function, function are computed for the energy range of 30eV. The static refractive index for pure and TM-doped obtained are 2.87, 2.99 and 3.5 respectively. Upsurges in static dielectric constants are also sighted, predicting a shift from semiconducting to metallic behavior after TM doping in c-BiAlO3 . TM-doping has also boosted the absorption spectra response and reflectivity in the UV-region. Sc and Zn-doped c-BiAlO3 can be considered as potential materials in photovoltaic application.